Korean Media Strategies in Constructing Global Education Narratives: A Framing Analysis of SEVENTEEN's Speech at UNESCO - Rafilah, Cinta Najla Syifa; Triarisanti, Risa; Widyana, Ashanti (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
This research employs Pan and Kosicki's framing model to examine the depiction of SEVENTEEN's address at the 2023 UNESCO Youth Forum by Korean online media. The study analyzed three leading media sources: The Chosun Daily, Hankyoreh, and The Kyunghyang Shinmun, each showcasing distinct ideological perspectives. This research employs qualitative methods to explore how these outlets intentionally utilize syntactic, script, thematic, and rhetorical framing components to construct the conveyed message. The results indicate that The Chosun Daily prioritizes national pride and unity, Hankyoreh emphasizes humanitarian and educational themes, while The Kyunghyang Shinmun showcases youth empowerment and solidarity. Although they have differing ideologies, the three media organizations advocate for common principles, such as the significance of education, international collaboration, and leadership among young people. This research highlights the significant influence of framing on the public's views of global occurrences and personalities, particularly within the realm of public diplomacy via K-pop. Furthermore, it aids in the progression of media studies by offering perspectives on how cultural symbols shape stories of optimism, collaboration, and citizenship. Future comparative research is suggested to examine cross-cultural framing methods in digital journalism.